Modernitas Kehidupan Beragama Dalam Perkembangan Pendidikan Islam : (Studi Analisis Pemikiran Muhammad Abduh) - Jaelani, Juhri (Civilization Research: Journal of Islamic Studies, 2023)
Religion as a way to get to God makes people have different perspectives. This perspective does little to make humans have exclusive characteristics in religious life. This study aims to describe Muhammad Abduh's thoughts about the role of religion and education in national life. This study uses a qualitative approach with the method of literature (library research). Data collection techniques in this study used descriptive analysis methods by reading, understanding, studying and analyzing Muhammad Abduh's thoughts. The results of the study show that Muhammad Abduh places reason in its true position, namely reason is the main capital in carrying out religious and national life. As well as methods for developing good and right minds, one of which is through the educational process. So in the context of education, Muhammad Abduh gave an idea to adjust the fulfillment of learning material between the needs of the mind and the soul so that it becomes balanced and can obtain happiness in this world and in the hereafter.